Impaired social functioning in children with narcolepsy. Issue 2 (23rd November 2018) - Quaedackers, Laury; van Gilst, Merel M; van Mierlo, Petra; Lammers, Gert-Jan; Dhondt, Karlien; Amesz, Pauline; Peeters, Els; Hendriks, Danielle; Vandenbussche, Nele; Pillen, Sigrid; Overeem, Sebastiaan
Abstract: Study Objectives: To explore impairments in social functioning in children with narcolepsy compared to healthy children. Methods: Parents of 53 pediatric patients with narcolepsy type 1 and 64 matched healthy children completed the Social Responsiveness Scale (SRS) and the Child Behavior Checklist 6–18 (CBCL 6–18). Results: Patients scored significantly higher on the total score of the SRS (median 56, interquartile range [IQR] 23.5) compared to controls (median 44.5, IQR 8.5, U = 797.0, p < 0.001). Patients also scored higher on the sum of the CBCL 6–18 subscales indicative of social functioning (Withdrawn/Depressed, Social Problems, and Thought Problems; median 183, IQR 30.5) compared to controls (median 155, IQR 13, U = 500.0, p < 0.001). A total of 24 patients (45.3%) reported at least mild-to-moderate difficulties in social functioning compared to seven controls (10.9%, χ 2 = 17.165, p < 0.001). Eleven patients (20.8%) and only one control (1.6%) had T scores above 75, which points to severely impaired social functioning (χ 2 = 11.602, p = 0.001). Within the patient group, girls reported mild-to-moderate difficulties in social functioning significantly more often compared to boys on the SRS (77.8% versus 28.6%, χ 2 = 17.560, p < 0.001). Conclusions: Impaired social functioning is common in children with narcolepsy type 1, especially in girls. Questionnaires such as the SRS and the CBCL 6–18 may help in early detection of social problems in pediatric narcolepsy. Recognition of these problems could be valuable in the management of young people with narcolepsy.